Prevalence and characteristics of registered falls in a Belgian University Psychiatric Hospital - de Smet, Lynn; Carpels, Arnout; Creten, Lotte; De Pauw, Louise; Van Eldere, Laura; Desplenter, Franciska; De Hert, Marc (Frontiers in Public Health, 2022)
Objectives: Falls in elderly patients treated in general hospitals have already been the focus of several studies. Research within psychiatric settings, however, remains limited, despite the fact that this population has a number of characteristics that could increase the fall risk. The aim of this retrospective study was to estimate the prevalence of falling in patients with a psychiatric hospital setting. Methods: A retrospective descriptive chart review of falls registered in the period July 1, 2013 until June 30, 2019 in a Belgian University Psychiatric Hospital was conducted. Data were collected from the ‘patient related incident report and management system’ (PiMS) of the hospital. All registered falls of all hospitalized patients were included in the study. Results: During the 6-year study period an incidence of 4.4 falls per 1,000 patient days was found. Only 0.5% of the falls resulted in severe injury and none of these falls were fatal. Eighty percent of falls involved a patient over the age of 65. Only 25.0% of the elderly patients suffered physical consequences, while injuries were present in 31.4% of adults and 68.2% of young patients. The two most common causes of a fall were the health status (63.3%) and the behavior (55.1%) of the patient. Conclusion: The estimated prevalence of falls in our study was generally in line with the rates found in literature on falls in psychiatric settings. Falls in psychiatric settings occur both in younger and older patients, suggesting that all age categories deserve sufficient attention in fall prevention policies. However, more research is necessary to improve fall prevention policies.